Відповідь:
19x-11y+12=0
Покрокове пояснення:Simplifying
19x + -11y + 12 = 0
Reorder the terms:
12 + 19x + -11y = 0
Solving
12 + 19x + -11y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + 19x + -12 + -11y = 0 + -12
Reorder the terms:
12 + -12 + 19x + -11y = 0 + -12
Combine like terms: 12 + -12 = 0
0 + 19x + -11y = 0 + -12
19x + -11y = 0 + -12
Combine like terms: 0 + -12 = -12
19x + -11y = -12
Add '11y' to each side of the equation.
19x + -11y + 11y = -12 + 11y
Combine like terms: -11y + 11y = 0
19x + 0 = -12 + 11y
19x = -12 + 11y
Divide each side by '19'.
x = -0.6315789474 + 0.5789473684y
Simplifying
x = -0.6315789474 + 0.5789473684y
не существует y(x) > 0 y(x) < 0 y(x) > 0
-4 -3 -2 >x
не существует F(x) возрастает убывает возрастает
Точка максимума функции F(x) равна x=-3
Далее находим производную y'(x) = ln(x+4) + (x+2) / (x+4)
Находим значение в ней: y'(-3) = ln(-3+4) + (-3+2) / (-3+4) = -1